Implementing the online game Mobile Legends: Bang Bang to support students’ English vocabulary learning - Asih Dayanti, Asih Dayanti; Yuliati (ELT Forum: Journal of English Language Teaching, 2025)
This study explores the integration of Mobile Legend Bang-Bang (MLBB) to support vocabulary learning, applying Notion’s (2001) framework of noticing, retrieval, and generation. Most studies focus on how MLBB functions to promote vocabulary outcomes; however; there is a gap in exploring the cognitive processes behind vocabulary acquisition hero quotes from the game. This research seeks to fill that gap by clarifying how hero quotes assist in vocabulary learning. With a qualitative case study design at at a vocational high school in Indonesia, data collected included classroom observations and interviews with thirty-three students and one English teacher. The results indicated that MLBB helps foster vocabulary noticing, remembering, and using words. Furthermore, students were more digitally interested as well as more imaginatively engaged cognitively with the material. Teachers reported improved student participation along with more creative lesson planning, greater digital engagement, and instructional flexibility tailored to learners’ levels. The study concludes that controlled usage of MLBB leads to purposeful vocabulary learning, indicating that game-centered media have positive impacts on language teaching and learning in classrooms designed for digital natives. Practical implementation may include quote-based noticing tasks, retrieval games, expressive production activities, and structured teacher mediation to optimize learning outcomes.